2022
DOI: 10.3847/1538-4357/ac32be
|View full text |Cite
|
Sign up to set email alerts
|

The Eccentric Nature of Eccentric Tidal Disruption Events

Abstract: Upon entering the tidal sphere of a supermassive black hole, a star is ripped apart by tides and transformed into a stream of debris. The ultimate fate of that debris, and the properties of the bright flare that is produced and observed, depends on a number of parameters, including the energy of the center of mass of the original star. Here we present the results of a set of smoothed particle hydrodynamics simulations in which a 1M ⊙, γ = 5/3 polytrope is disrupted by a 106 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Hammerstein et al (2022) defined three types of behavior for the UV/optical light curves, labeling them power-law decay (with indices ranging from -1 to -3 and a sizable fraction that decay consistent with a t −5/3 law), plateau, and structured light curves. Deviations from the late-time t −5/3 decay have also been suggested theoretically; Hayasaki et al (2013) and Cufari et al (2022a) found that stars on eccentric orbits can lead to a prompt shutoff in the light curve, while Guillochon & Ramirez-Ruiz (2013) found that partial TDEs-in which the dense stellar core survives the tidal encounter with the SMBH-can lead to significant deviations from t −5/3 . predicted that partial TDEs should generically exhibit a t −9/4 decay.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Hammerstein et al (2022) defined three types of behavior for the UV/optical light curves, labeling them power-law decay (with indices ranging from -1 to -3 and a sizable fraction that decay consistent with a t −5/3 law), plateau, and structured light curves. Deviations from the late-time t −5/3 decay have also been suggested theoretically; Hayasaki et al (2013) and Cufari et al (2022a) found that stars on eccentric orbits can lead to a prompt shutoff in the light curve, while Guillochon & Ramirez-Ruiz (2013) found that partial TDEs-in which the dense stellar core survives the tidal encounter with the SMBH-can lead to significant deviations from t −5/3 . predicted that partial TDEs should generically exhibit a t −9/4 decay.…”
Section: Introductionmentioning
confidence: 63%
“…The partially disrupted star was captured onto a relatively tight orbit through the destruction of the binary (i.e., Hills capture), thus generating a repeating, partial TDE (as well as a high-velocity star flung out from the system) and the late-time flare. This model is not only consistent with the observations but also predicts that (1) the fallback time of the tidally stripped debris is ∼600 days (a timescale that is, we note, ordinarily very hard to constrain from observations of full TDEs), (2) the orbital time of the captured star is ∼1200 days, and (3) the source should once again dim at day ∼1800 (when the core is expected to return again) and brighten a third time at day ∼2400 if the star was not completely destroyed on its second pericenter passage; on the other hand, if it was completely destroyed, we would expect-as it is then an ordinary TDE-a roughly power-law decay in its luminosity (although, if the star is on a bound orbit, it may exhibit a double-peaked light curve, depending on the eccentricity; Cufari et al 2022a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it was not our focus here, we also analyzed the disruption of the same star with β = 8, and while the stream displayed vigorous fragmentation into smallscale clumps (under its own self-gravity, in line with recent predictions and simulations that suggest that self-gravity is important at late times for high-β encounters; Steinberg et al 2019;Coughlin et al 2020b;Nixon et al 2021), one clump near the geometric center of the stream had a density increased above the others by a factor of ∼ 10 and correspondingly a much larger mass than the rest. This suggests that β = 8 may also exhibit core reformation, but the mass contained in the core is insufficient to prevent further fragmentation (see the discussion in Cufari et al 2022). More generally, this finding implies that there is nothing unique about β = 16, and that the transition between fragmentation and single core reformation, both of which are ultimately due to the same instability (Coughlin & Nixon 2015), lies somewhere between β = 8 and 16.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present the results of numerical simulations of disruptions of Sun-like stars modeled with the Eddington standard model. We use the smoothed-particle hydrodynamics (SPH) code PHANTOM (Price et al 2018), which has been widely used for studying TDEs (Coughlin & Nixon 2015;Coughlin et al 2016;Miles et al 2020;Norman et al 2021;Cufari et al 2022).…”
Section: Simulation Setupmentioning
confidence: 99%